Spatial-Temporal Distribution of Allelopathic Rice Roots in Paddy Soil and Its Impact on Weed-Suppressive Activity at the Seedling Stages - Li, Jiayu; Lin, Shunxian; Ma, Huayan; Wang, Yanping; He, Haibin; Fang, Changxun (Frontiers in Plant Science, 2022)
Background Allelochemicals secreted by allelopathic rice roots are transmitted to the receptor rhizosphere through the soil medium to inhibit the growth of the surrounding weeds. This research aimed to explore the relationships between the spatial-temporal distribution of rice roots in soil and weed-suppression ability at its seedling stage. Results This study first examined the root distribution of three rice cultivars in paddy soil in both vertical and horizontal directions at 3–6 leaf stage. Then, an experiment using rice–barnyardgrass mixed culture was conducted to analyze the allelopathic potential and allelochemical content secreted by rice roots in different lateral soil layers. The results showed that allelopathic rice had a smaller root diameter and larger root length density, root surface area density, and root dry weight density than those of non-allelopathic rice, in the top 5 cm at 5- and 6-leaf stages. In particular, there were significant differences in root distribution at the horizontal distance of 6–12 cm. Besides, allelopathic rice significantly inhibited the above-ground growth of barnyardgrass co-cultured at 12 cm lateral distance in situ, and the content of benzoic acid derivatives in allelopathic rice in a 6–12 cm soil circle was higher than that observed at 0–6 cm distance. Moreover, correlation analysis confirmed that the distribution of roots in the horizontal distance was significantly correlated with weed inhibition effect and allelochemical content. Conclusion These results implied that spatial distribution of allelopathic rice roots in paddy soil, particularly at the lateral distance, appears to have important impact on its weed-suppressive activity at the seedling stage, suggesting that modifying root distribution in soil may be a novel method to strengthen the ability of rice seedlings to resist paddy weeds.